Floristic profile and community structure of the herbaceous dune vegetation (“restinga”) located in Ilhas, municipality of Araranguá, Santa Catarina, Brazil - Robson dos Santos; Vanilde Citadini-Zanette; Alecsandro Schardosim Klein (Biotemas, 2007)
The purpose of this study was to elucidate the floristic composition and community structure of the herbaceous dune vegetation (“restinga”) in Ilhas, Araranguá, Santa Catarina. For the floristic survey a selective walking method was used, and for the phytosociological study the plot method was employed. Six transect units separated by a distance of about 600m were made up of five 4m2 plots, giving a total of 30 plots (120m2). Species cover was estimated according to the scale proposed by Causton. Sixty species and 30 families were registered. The richest families were Asteraceae (11) and Poaceae (nine). The species with highest importance values were Juncus acutus L., Andropogon arenarius Hack. and Hydrocotyle bonariensis Lam. Species diversity and evenness, using the indexes of Shannon (H') and Pielou (J), with regard to frequency, were 3.25 nats and 0.60, respectively.